PRIMARY SCHOOL TEACHERS' PRE-SERVICE TRAINING: THE EXPERIENCE OF ISRAEL - Natalia Bakhmat (Pavlo Tychyna Uman State Pedagogical University, 2019)
The article reveals the peculiarities of professional and pedagogical prepa-ration of primary school teachers, which are considered to be a prerequisite for determining the effective directions of the Ukrainian educational system develop-ment in the conditions of its reformation. It was found that initial professional education in Israel takes place in pedagogical colleges and universities. There are eight universities in the country characterized by multi-disciplinarity, training, teaching and research in various fields of knowledge; this provides a wide range of specialities and a diverse range of training areas. Educa-tional institutions implement two directions of education: academic and studying for the degree of a certified teacher through the provision of vocational and pedago-gical education. High educational institutions are divided into 3 categories: those that are recognized by the Council for Higher Education, award the first academic degree in pedagogy -- B.Ed (4 years of study) and a certificate of the Ministry of Education (3 years of study); educational establishments that give a certificate of the Ministry of Education (3 years of study); Colleges of Independent Religious Edu-cation (working under the control of the Ministry of Education). Among the main progressive trends in updating the contents of the Israeli higher professional education are the intensive development and implementation of curricula that have an interdisciplinary and problematic character; differentiation and individualization of the content of education, reproduced in the modular organi-zation of the educational process, the use of variation programs, the free choice of disciplines and the object of research within the program; integration of learning with practical activities by increasing the time for pedagogical practice, the intro-duction of various forms of organization of pedagogical activities during training and postgraduate qualification improvement. A detailed review of Israeli electronic educational resources allowed making the assumptions about their large numbers and diversity, but their use requires payment.